Decision Criteria to Tobacco Biofuel Production - Schneider, Rosana de Cassia de Souza; Carvalho, Fernando Sansone de; Moraes, Jorge André Ribas; Nara, Elpídio Oscar Benitez (Journal of Agriculture and Environment for International Development (JAEID), 2021)
This work presents a study to identify the potential of biofuel production from an energetic tobacco. The objective is to establish a priority scale under specific criteria for the possibilities of biofuels which have already been studied from various plants. This will provide a direction for research that aims to investigate biofuels, directing their efforts based on the priorities found. The priorities were obtained through multicriterial analysis, based on criteria chosen by the SAATY scale and defined with the DELPHI method. After being analyzed in WebPROA software to determine the order of importance using three methods: Borda, Condorcet, and Copeland, all indicated that biodiesel and bioethanol are the two priority fuels for development of studies of energy tobacco biofuels.